Numeracy-Based Teaching Material with Data Presentation Topic to Support Students' Numeracy Skills - Situmorang, Gresilia; Hapizah, Hapizah; Mulyono, Budi; Susanti, Ely (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
Numeracy is the ability to identify, describe and communicate various types of numbers and mathematical symbols to solve mathematical tables, graphs, and problems. There are few math teaching materials, especially those based on numeracy. The research aims to produce numeracy-based teaching material that is valid, practical and potentially supports numeracy skills. The following type of research is development. The research subjects were students of class VII at Senior high school in Pagar Aam. The stages of the research consisted of preliminary study and formative evaluation (Expert Review, One to One, Small Group and field tests) with the instruments used, namely questionnaires, tests, and interviews. This study states that the teaching material used can help improve numeracy skills, and the developed teaching material is declared valid without revision. This shows that with the help of numeracy-based teaching, the material can help students improve their numeracy skills in understanding data presentation material. Mathematics teachers can further use these numeracy-based teaching materials to improve students’ numeracy skills.Numerasi adalah kemampuan untuk mengidentifikasi, menjelaskan dan mengkomunikasikan berbagai jenis bilangan dan simbol matematika untuk tujuan pemecahan tabel, grafik dan masalah matematika. Belum banyak bahan ajar matematika khususnya yang berbasis numerasi. Tujuan penelitian ialah menghasilkan bahan ajar berbasis numerasi yang valid, praktis dan berpotensi mendukung kemampuan numerasi. Jenis penelitian ialah  pengembangan. Subjek penelitian adalah peserta didik kelas  VII  disalah satu  SMP Negeri di Kota Pagar Alam. Tahapan penelitian terdiri dari  preliminary study dan formative evaluation (Expert Review, One to One, Small Group dan field test) dengan instrumen yang digunakan yaitu angket, tes dan  wawancara. Penelitian ini menyatakan bahwa bahan ajar yang dikembangkan dinyatakan valid, praktis, dan memiliki efek potensial terhadap kemampuan numerasi peserta didik. Hal ini menunjukkan bahwa dengan bantuan bahan ajar berbasis numerasi dapat membantu peserta didik menumbuhkan kemampuan numerasi peserta didik khususnya  materi penyajian data. Bahan ajar berbasis numerasi ini dapat digunakan guru dalam mendukung kemampuan numerasi peserta didik.